The Effects of Synchronous Computer-Mediated Interaction and Face-to-Face Interaction on Iranian EFL Learners’ Speaking and Listening Anxiety - Parisa Moradi; Abbas Ali Zarei (Journal of Modern Research in English Language Studies)
Although technology has greatly influenced different aspects of language learning, the nature and the extent to which it influences learners’ anxiety in oral skills remains a contentious issue. The primary objective of this study was to examine how synchronous computer-mediated interaction (SCMI) and face-to-face (FTF) interaction influence speaking and listening anxiety among Iranian EFL learners. The study involved 60 male and female English language learners at Kish-e-Mehr language institute and Dialog Online language institute in Qazvin, with ages ranging from 15 to 35. Convenience sampling based on availability was used to select the participants. Initially, the participants completed questionnaires assessing their speaking anxiety and listening anxiety as pretests; this was followed by 12 treatment sessions. After these sessions, they filled out the same questionnaires again as posttests. The data collected were analyzed using one-way ANCOVA, the results of which revealed that SCMI effectively reduced both speaking anxiety and listening anxiety. This study highlights the potential of SCMI as a practical approach to reduce speaking and listening anxiety. The results of this study can have significant implications for language teachers, learners, and material developers